SAUDI ARABIA ISLAMOPHILIA: RECONSTRUCTING CONSERVATIVE ISLAM INTO MODERATE ISLAM THROUGH FOOTBALL - Auliyaur Rachman; Ahmad Salehudin (CMES (Center of Middle Eastern Studies), 2025)
This study explores the reform of football in Saudi Arabia in the context of the Saudi Vision 2030 initiative, which aims to reduce the Kingdom’s economic dependence on oil and gas resources. Employing a descriptive qualitative approach and library research method, the study is grounded in Alexander Wendt’s constructivist theory. The research investigates how Vision 2030 has influenced the lives of Saudi citizens and international visitors, particularly global football stars. Findings suggest that the vision, spearheaded by Crown Prince Mohammed bin Salman, has introduced substantial policy shifts that promote a more socially open, religiously moderate, and internationally welcoming environment. These reforms have not only transformed Saudi Arabia’s domestic landscape but also positioned football players as informal cultural ambassadors. Their presence serves to project a positive image of Saudi Arabia, countering Islamophobic narratives, especially in the Western world, by fostering what can be described as Islamophilia through sports diplomacy.